2017
DOI: 10.1073/pnas.1620879114
|View full text |Cite
|
Sign up to set email alerts
|

Differential control of retrovirus silencing in embryonic cells by proteasomal regulation of the ZFP809 retroviral repressor

Abstract: Replication of the murine leukemia viruses is strongly suppressed in mouse embryonic stem (ES) cells. Proviral DNAs are formed normally but are then silenced by a large complex bound to DNA by the ES cell-specific zinc-finger protein ZFP809. We show here that ZFP809 expression is not regulated by transcription but rather by protein turnover: ZFP809 protein is stable in embryonic cells but highly unstable in differentiated cells. The protein is heavily modified by the accumulation of polyubiquitin chains in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…We speculated that CDK2 might be partially degraded by a proteasome. We treated the cells with CHX to stop translation, along with MG132, an effective inhibitor of proteasomes, or DMSO as control [ 46 ]. CDK2 protein levels at the indicated time points (0 h, 12 h and 24 h after treatment) were monitored by western blot assay.…”
Section: Resultsmentioning
confidence: 99%
“…We speculated that CDK2 might be partially degraded by a proteasome. We treated the cells with CHX to stop translation, along with MG132, an effective inhibitor of proteasomes, or DMSO as control [ 46 ]. CDK2 protein levels at the indicated time points (0 h, 12 h and 24 h after treatment) were monitored by western blot assay.…”
Section: Resultsmentioning
confidence: 99%
“…We found that a cohort of KZNFs are widely expressed at the mRNA and protein level in human cells and may restrict incoming retroviruses. Intriguingly, the mouse KZFP, ZFP809 is rapidly degraded at the protein level in mouse differentiated cells, restricting its potency mainly to ESCs . An open question is whether KZNF expression is modulated by viruses, interferon treatment, or other stimuli as an antiviral strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation is needed to determine how ZNF268a is regulated during viral infection, although there is no significant change in ZNF268a transcript expression or total protein expression (data not shown). In addition, even when it is forcibly expressed in cells, the expression efficiency of ZNF268a is quite poor, a feature also seen with ZFP809 [21,42], possibly indicating tight control of ZNF268a within cells, which could explain the reason why sometimes the reintroduction of exogenously expressed ZNF268a only partially restored the activation of NF-κB as seen in Figures 3G and 5B. Detailed knowledge is also needed of whether other ZNF268a-associated proteins play roles in NF-κB regulation, and whether ZNF268a has any effects on the virus-induced interferon-dependent innate immune response by means of crosstalk between the immune-response pathways.…”
Section: Discussionmentioning
confidence: 99%